Karakteristik edible coating gel Aloe vera dengan fortifikasi bawang putih sebagai antimikroba - Jefri Pandu Hidayat; Hammada Alfafa Romadhona; Siti Munfarida; Ni’matus Sholihah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Aloe vera-based edible coating consists of hydrocolloids that have potential research to optimate the biodegradable bushing. Meanwhile, the process of edible coating Aloe vera characterization is still the mind concept. The investigation Aloe vera edible coating Aloe vera- is concluded lifetime storage which `still in development. Optimization of storage tight to surrounding microbial contamination. Adding antimicrobial matter that can sustain food precursors is one concept of packaging bio-transformation. Onion powder has antioxidant goods to be fathomed to increase the characteristic of edible coating.The aim research was determined the optimum formulation to get foremost option of biodegredable packaging technology by fortification method. The derivation viscosity model was added by first-order differential. Mixing with 2% w/v onion powder and Aloe vera suspension with five ratio variables (A-E) revisited the viscosity effect against storage time and microbial growth. Hereafter, the solution's impact over in simple modulation inhibits Aspergillus niger and common bacterial at ambient growth. One-way analysis of variance (ANOVA) was performed. In five days, the suspension shows decreasing viscosity. Stable at 40 cp on control variable without any addition after days. Onion powder fortified in the suspension depicts bacterial growth at 12 hours. Afterward, the zone of accretion bacterial is uncontrol. The best option for edible coating by water and Aloe vera is an equal ratio of either A. Niger and common bacteria up to 16 hours saving time. All storage at the ambient temperature of 28ºC. Further research on suspension Aloe vera edible coating needs to compare the other microbial substance addiction. Furthermore, the application to foodstuffs is a potential discussion of edible coating research.